2015
DOI: 10.1523/jneurosci.3841-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

The Increased Sensitivity of Irregular Peripheral Canal and Otolith Vestibular Afferents Optimizes their Encoding of Natural Stimuli

Abstract: Efficient processing of incoming sensory input is essential for an organism's survival. A growing body of evidence suggests that sensory systems have developed coding strategies that are constrained by the statistics of the natural environment. Consequently, it is necessary to first characterize neural responses to natural stimuli to uncover the coding strategies used by a given sensory system. Here we report for the first time the statistics of vestibular rotational and translational stimuli experienced by rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 51 publications
0
60
2
Order By: Relevance
“…The dataset was the same as that previously published (Schneider et al . ); however, we note that Schneider et al . () did not consider the spectral content of the recorded signals.…”
Section: Methodscontrasting
confidence: 76%
“…The dataset was the same as that previously published (Schneider et al . ); however, we note that Schneider et al . () did not consider the spectral content of the recorded signals.…”
Section: Methodscontrasting
confidence: 76%
“…Indeed, this view is supported by numerous studies showing that both afferents and central neurons accurately encode the detailed time course of head rotations through linearly related changes in firing rate over a wide range of frequencies reviewed in refs 1, 5, 29. Moreover, prior investigations had established that both peripheral30 and central28 vestibular neurons can respond nonlinearly to single repetitions of naturalistic stimuli14. However, while this property is required for temporal coding, it is not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…We note that the stimuli used in the present study do not elicit simple (that is, rectification, saturation) static nonlinearities in either regular or irregular afferents530. To detect the presence of other nonlinearities in the response, we quantified correlations between the neuronal response R(t) and the stimulus S(t) using the stimulus-response (SR) coherence C SR (f) , as in ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these movements only covered the lower range of frequencies and amplitudes observed during active self-motion (Carriot et al, 2015). Moreover, despite the remarkable linearity of early vestibular information processing (Bagnall et al, 2008), the high amplitude of active movements might recruit vestibular afferents in a non-linear way (Schneider et al, 2015). In addition, studies in mice and monkeys have revealed that active and passive head movements are processed in fundamentally different ways within the vestibular nuclei (Cullen & Roy, 2004), which are highly interconnected with the caudal cerebellar vermis.…”
Section: Introductionmentioning
confidence: 99%